2004
DOI: 10.1111/j.1464-5491.2004.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Amylin replacement with pramlintide as an adjunct to insulin therapy improves long‐term glycaemic and weight control in Type 1 diabetes mellitus: a 1‐year, randomized controlled trial

Abstract: These results show that mealtime amylin replacement with pramlintide, as an adjunct to insulin therapy, improves long-term glycaemic and weight control in patients with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
259
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(271 citation statements)
references
References 41 publications
6
259
1
Order By: Relevance
“…rIAPP, which is nontoxic and does not form amyloid in vivo or in vitro, differs from hIAPP at six sites, including three proline residues at positions 25, 28, and 29 and the replacement of H18 by R. These substitutions significantly influence the aggregation behavior of the polypeptide, whereas the others are more conservative: F23 in the human peptide is replaced by L, and I26 by V. We used the following series of mutations to test the role of specific residues in membrane interactions: First, pramlintide (PM) is an analog of hIAPP, which contains the three proline substitutions found in rIAPP. The molecule does not form amyloid in dilute solution, is not toxic, and has been approved as a complement to insulin therapy for the treatment of diabetes (32). Comparison of hIAPP and PM allows us to probe the role of the three prolines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rIAPP, which is nontoxic and does not form amyloid in vivo or in vitro, differs from hIAPP at six sites, including three proline residues at positions 25, 28, and 29 and the replacement of H18 by R. These substitutions significantly influence the aggregation behavior of the polypeptide, whereas the others are more conservative: F23 in the human peptide is replaced by L, and I26 by V. We used the following series of mutations to test the role of specific residues in membrane interactions: First, pramlintide (PM) is an analog of hIAPP, which contains the three proline substitutions found in rIAPP. The molecule does not form amyloid in dilute solution, is not toxic, and has been approved as a complement to insulin therapy for the treatment of diabetes (32). Comparison of hIAPP and PM allows us to probe the role of the three prolines.…”
Section: Resultsmentioning
confidence: 99%
“…PM, N-methyl-IAPP, and rIAPP have been reported to be nontoxic (32,34,36). We tested the cytotoxicity of I26P-IAPP, DM-IAPP, rIAPP, and N-methyl-IAPP using rat insulinoma-1 (INS-1) β cells.…”
Section: Toxic and Nontoxic Variants Of Iapp Induce Model Membranementioning
confidence: 99%
“…Side effects of pramlintide administration are a likely reason; nausea, anorexia, vomiting and hypoglycemia are commonly reported adverse events (Whitehouse et al 2002, Ratner et al 2004, Edelman et al 2006) and appear to be worse in T1D than in T2D or obese individuals. The anorexia and nausea induced by pramlintide may also be factors in sustained weight loss and long-term improvements in glycemia.…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…Pramlintide can significantly decrease post-meal glucagon levels in type 1 diabetes mellitus and trials have also shown that pramlintide reduces glucose variability by delaying gastric emptying. [51][52][53][54][55] …”
Section: Amylinmentioning
confidence: 99%